Adaptive Banking Strategies to Address Embedded Finance Disruption in Digital Commerce Platforms - Tahu, Gregorius Paulus; Setiadi, Hendri; Verawati, Yenny (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores the impact of embedded finance disruption on traditional banking institutions within digital commerce platforms. The rapid integration of financial services such as payments, lending, and insurance into e-commerce platforms poses both challenges and opportunities for banks. The aim of this research is to identify adaptive strategies that banks can adopt to remain competitive in the face of this disruption. Using a library-based research methodology, data was collected from secondary sources, including books, academic journals, and industry reports. The findings reveal that banks are increasingly leveraging open banking, APIs, and digital transformation strategies to integrate their services into digital platforms. However, challenges related to regulatory compliance, data privacy, and organizational resistance remain significant barriers. In conclusion, banks must embrace innovation, collaborate with fintech companies, and develop flexible, customer-centric solutions to thrive in the evolving digital finance ecosystem.